Evolution of the insect Hox gene cluster: comparative analysis across 243 species - Mulhair, PO; Holland, PWH (Elsevier, 2022)
The Hox gene cluster is an iconic example of evolutionary conservation between divergent animal lineages, providing evidence for ancient similarities in the genetic control of embryonic development. However, there are differences between taxa in gene order, gene number and genomic organisation implying conservation is not absolute. There are also examples of radical functional change of Hox genes; for example, the ftz, zen and bcd genes in insects play roles in segmentation, extraembryonic membrane formation and body polarity, rather than specification of anteroposterior position. There have been detailed descriptions of Hox genes and Hox gene clusters in several insect species, including important model systems, but a large-scale overview has been lacking. Here we extend these studies using the publiclyavailable complete genome sequences of 243 insect species from 13 orders. We show that the insect Hox cluster is characterised by large intergenic distances, consistently extreme in Odonata, Orthoptera, Hemiptera and Trichoptera, and always larger between the ‘posterior’ Hox genes. We find duplications of ftz and zen in many species and multiple independent cluster breaks, although certain modules of neighbouring genes are rarely broken apart suggesting some organisational constraints. As more high-quality genomes are obtained, a challenge will be to relate structural genomic changes to phenotypic change across insect phylogeny.